Knowledge, Perception and Satisfaction with the Quality of Care among Medical and Surgical Outpatient Clinics Attendees in a Nigerian Tertiary Hospital - Adeyemi, Dunsin Tomisin; Kolawole, Ifeoluwapo Oluwafunke; Ndikom, Chizoma Millicent (Inspirasi Foundation, 2024)
Introduction: Improving the quality of healthcare remains a critical need in developing countries. Donabedian’s quality of care model provides a framework to evaluate healthcare outcomes, with patient satisfaction being a key indicator. Understanding patients' perceptions, knowledge, and satisfaction is essential for enhancing healthcare delivery. Objective: This study aimed to assess patients' perceptions, knowledge, and satisfaction with the quality of care provided at a tertiary hospital in Ibadan, Nigeria. Method: A total of 401 individuals were recruited, and data was collected using a self-administered questionnaire. Data were coded, cleaned, and analyzed using SPSS version 20. Descriptive statistics were summarized in frequency tables and figures, while Chi-square tests were used to test hypotheses at a significance level of p<0.05. Result: Out of 350 valid responses, 86% of respondents demonstrated substantial knowledge about the quality of care. However, 57.1% expressed dissatisfaction with the treatment received, while 56.6% maintained a positive perception of the hospital’s services. A significant relationship was found between knowledge of healthcare quality and perception (χ2 = 11.1, df = 1, p<0.05). On the other hand, the duration of hospital stay did not significantly affect overall satisfaction (χ2 = 0.69, df = 2, p = 0.708). Conclusion: The findings highlight the need to enhance patient satisfaction in healthcare services. Periodic investigations into patient perspectives are essential for informed decision-making and continuous quality improvement in healthcare delivery.